1975
DOI: 10.1080/00222895.1975.10735018
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Location and Distance in Reproducing Different Amplitudes of Movement

Abstract: Experiments have demonstrated that in order to reproduce a standard movement, subjects can move for a certain distance or move to a certain location. Available evidence tentatively suggests the use of distance for short movements and location for long movements. However, this evidence is in conflict with the motor short-term memory characteristics of short and long movements. An experiment is reported which demonstrates that subjects spontaneously use distance for short movements and location for long movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0
3

Year Published

1978
1978
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 14 publications
1
15
0
3
Order By: Relevance
“…One line of evidence had suggested that distance cues were primarily used in the reproduction of short move- Location Reproduction ments, while location cues principally subserved the reproduction of long movements (Gundry, 1975;Keele, 1968;Keele & Ells, 1972;Marteniuk & Roy, 1972;, Roy & Kelso, 1977Stelmach, 1970;Stelmach et al, 1975). In another series of experiments, distance was reported to be a pervasive cue in the reproduction of end locations for a variety of movement lengths (Walsh, 1981;, 1980Walsh et al, , 1981.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…One line of evidence had suggested that distance cues were primarily used in the reproduction of short move- Location Reproduction ments, while location cues principally subserved the reproduction of long movements (Gundry, 1975;Keele, 1968;Keele & Ells, 1972;Marteniuk & Roy, 1972;, Roy & Kelso, 1977Stelmach, 1970;Stelmach et al, 1975). In another series of experiments, distance was reported to be a pervasive cue in the reproduction of end locations for a variety of movement lengths (Walsh, 1981;, 1980Walsh et al, , 1981.…”
Section: Discussionmentioning
confidence: 95%
“…A pervasive effect of distance information on the reproduction of terminal location has been reported for movements varying in length from 8 em (Walsh, 1981) to 40 em Walsh et al, , 1981. Consequently, such evidence has been used to argue against the view (Keele, 1968;Stelmach, Kelso, & Wallace, 1975;Gundry, 1975;Roy & Kelso, 1977) that subjects utilize location cues to remember long movements.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…The intent underlying this question was to evaluate a possible source of error that seemed evident in the design of motor short-term memory studies. A research strategy typically used is to select a limited number of criterion positions and to test each of these positions repeatedly with the same subject, once under several experimental conditions (Craft, 1973;Craft & Hinrichs, 1971;Diewert, 1975;Duffy, Montague, Laabs, & Hillix, 1975;Gundry, 1975;Laabs, 1973Laabs, , 1974Marteniuk, 1973;Marteniuk & Roy, 1972a, 1972bShea, 1977;Stelmach & Walsh, 1973;Stelmach & Wilson, 1970). As discussed elsewhere (Gentile, 1974), this strategy seems analogous to studying verbal short-term memory by presenting a subject with the same trigram over and again for all experimental treatments.…”
mentioning
confidence: 97%